Miniaturized Band Pass Filter in Substrate Integrated WaveguideTechnology - Parameswaran, Ananya; P, Athira; Raghavan, S (International Journal of Engineering and Technology, 2018)
Miniaturization is an important criteria in the selection of devices for next generation communication systems. A novel miniaturization technique for an inductive post filter is investigated in this paper. Miniaturization is not so popular in inductive post Substrate Integrated Waveguide (SIW) filter and so considerable amount of research is to be done in this domain. A band pass filter in SIW technology using inductive posts is realized and further analyses are carried out. The insertion loss in the pass band is found to be 0.5 dB and the return loss is 22 dB. In this paper, we investigate the use of slow wave technology for miniaturization. Unlike the conventional SIW, the slow wave SIW topology requires a double layer substrate with internal metallized vias introduced in the bottom layer connected to the bottom conductive plane. The number of rows of internal metallized vias was chosen based on a parametric study. The proposed miniaturization technique shows that the SIW filter is 21.6 % and 34.6 % miniaturized in size and area respectively. The response of the filter covers Ka band and hence is suitable for satellite communication application. A quality factor of 506 is achieved for the miniaturized filter.Â Â